Endometriosis shows no impact on the euploid blastocyst rate per cohort of inseminated metaphase-II oocytes: A case-control study. (January 2021) - Vaiarelli, Alberto; Venturella, Roberta; Cimadomo, Danilo; Conforti, Alessandro; Pedri, Sara; Bitonti, Giovanna; Iussig, Benedetta; Gentile, Cinzia; Alviggi, Erminia; Santopaolo, Serena; Zullo, Fulvio; Rienzi, Laura; et al.
Abstract: Objective: To evaluate the true impact of endometriosis on oocytes' competence defined as blastulation, euploidy and implantation rates. Design: Retrospective multicenter case-control study involving infertile couples undergoing ICSI with qPCR and trophectoderm biopsy-based PGT-A. Patients affected from endometriosis (n = 210) were diagnosed through transvaginal sonography or surgical history with histological confirmation. Each case was matched to two controls (n = 420) according to IVF clinic, maternal age at retrieval (38.6 ± 2.7 yr), number of previous failed IVF treatments (0.5 ± 0.8) and number of metaphase-II oocytes retrieved (6.1 ± 3.7 per patient). The primary outcome was the mean euploid blastocyst rate per cohort of inseminated metaphase-II oocytes. Other embryological, clinical, obstetric and neonatal outcomes were also evaluated. Results: The mean euploid blastocyst rate per cohort of inseminated metaphase-II oocytes was identical in the two groups (18 %±22 %) independently of maternal age. No difference was shown for all embryological outcomes investigated. The live birth rates per vitrified-warmed single euploid blastocyst transfer were also similar (67/158, 42 % in patients affected from endometriosis versus 132/327, 40 % in matched-controls). No difference was reported in the gestational and neonatal outcomes. The cumulative live birth delivery rates among completed cycles were also identical (61/201, 30 % versus 117/391, 30 % in endometriosis and matched-control groups, respectively) independently of maternal age. Conclusions: Endometriosis might not impair oocyte developmental and reproductive competence, although its potential impact on the number of metaphase-II oocytes retrieved cannot be ignored. This information is critical for clinicians during counseling to outline an effective strategy to treat infertile patients affected from this condition. Future prospective studies are needed to evaluate the impact of endometriosis stage on euploidy rates.